Nitrous oxide production in sputum from cystic fibrosis patients with chronic Pseudomonas aeruginosa lung infection - Hansen, Christine Rønne (2014)
Chronic lung infection by Pseudomonas aeruginosa is the major severe complication in cystic fibrosis (CF) patients, where P. aeruginosa persists and grows in biofilms in the endobronchial mucus under hypoxic conditions. Numerous polymorphonuclear leukocytes (PMNs) surround the biofilms and create local anoxia by consuming the majority of O2 for production of reactive oxygen species (ROS). We hypothesized that P. aeruginosa acquires energy for growth in anaerobic endobronchial mucus by denitrification, which can be demonstrated by production of nitrous oxide (N2O), an intermediate in the denitrification pathway. We measured N2O and O2 with electrochemical microsensors in 8 freshly expectorated sputum samples from 7 CF patients with chronic P. aeruginosa infection. The concentrations of NO3− and NO2− in sputum were estimated by the Griess reagent. We found a maximum median concentration of 41.8 µM N2O (range 1.4–157.9 µM N2O). The concentration of N2O in the sputum was higher below the oxygenated layers. In 4 samples the N2O concentration increased during the initial 6 h of measurements before decreasing for approximately 6 h. Concomitantly, the concentration of NO3− decreased in sputum during 24 hours of incubation. We demonstrate for the first time production of N2O in clinical material from infected human airways indicating pathogenic metabolism based on denitrification. Therefore, P. aeruginosa may acquire energy for growth by denitrification in anoxic endobronchial mucus in CF patients. Such ability for anaerobic growth may be a hitherto ignored key aspect of chronic P. aeruginosa infections that can inform new strategies for treatment and prevention.